MIMO-OFDM System For Single RF Antenna Schemes with Convolutional Coding - I Gede Puja Astawa, Amang Sudarsono, Tri Budi Santoso, Prima Kristalina, Nihayatus Saadah (International Conference on Industrial Revolution for Polytechnic Education, 2020)
Multiple Input Multiple Output (MIMO) system use multiple transmit and receive antennas to increase data rate without expanding bandwidth. The combination of MIMO system with Orthogonal Frequency Division Multiplexing (OFDM) can provide greater throughput and provide the quality of high-speed information in real time. Multi antenna in MIMO system cause large power consumption. The latest technology in antenna system to overcome high power consumption is antenna based on single Radio Frequency (RF). The antenna system with single RF energy that can minimize lower cost. In this research, the MIMO-OFDM system uses channel coding that can avoid noise is convolutional coding. We evaluate the performance of MIMO-OFDM system for single RF antennas by creating a simulation program computers. The simulation demonstrate that MIMO-OFDM system using single RF antenna and using convolutional coding with rate ¼ is better 7 dB than without convolutional coding. The result of this paper is performance of the system is expressed in the form of the curve of BER as a function of SNR.